IMPLEMENTATION OF THE “7 HABITS OF GREAT INDONESIAN CHILDREN” MOVEMENT TO ENHANCE CHARACTER DEVELOPMENT AMONG ELEMENTARY SCHOOL STUDENTS - Sauriyah Haryati; Ana Fitrotun Nisa (RADJA PUBLIKA, 2025)
This study aims to analyze the implementation of the Seven Habits of Highly Effective Children movement in strengthening elementary school students’ character through a Systematic Literature Review (SLR) supported by bibliometric analysis using the VOSviewer software. Data were obtained from national and international scholarly articles published between 2015 and 2025, sourced from databases such as Google Scholar, Scopus, DOAJ, and Sinta. Article selection was conducted using inclusion and exclusion criteria to ensure relevance to the topics of character education and habit formation in elementary schools. The findings reveal that the application of the Seven Habits of Highly Effective Children has effectively reinforced key character values, including discipline, responsibility, cooperation, and independence. The most frequently employed habituation strategies include morning routines, daily reflection activities, teacher role modeling, and collaboration with parents. Bibliometric analysis indicates a growing trend in research on character education at the elementary school level, although studies that specifically integrate the Seven Habits framework remain relatively limited. This suggests the need for further research to develop more innovative approaches aligned with 21st-century educational demands. Supporting factors for program success include school commitment, teacher consistency, and parental involvement, while inhibiting factors involve time constraints, limited resources, and insufficient continuity of habituation outside the school environment. These findings indicate that program success depends not only on schools but also on broader environmental support. Thus, the implementation of the Seven Habits of Highly Effective Children movement has the potential to serve as an effective strategy in fostering morally upright, independent, and adaptive elementary school students prepared for contemporary challenges.